MUC5B regulates alterations in the immune microenvironment in nasopharyngeal carcinoma via the Wnt/β-catenin signaling pathway - Hongming Wang (Discover Oncology)
Abstract Objective To screen potential differentially expressed genes related to immune function in nasopharyngeal carcinoma through an online database, and to verify their mechanism of action, so as to provide a reference for the diagnosis and treatment of nasopharyngeal carcinoma in the future. Methods Differentially expressed genes were analyzed from the GSE227541 dataset, and functional enrichment analysis was conducted. With mucin 5B, oligomeric mucus/gel-forming as the focus, the correlation between its expression and immune indexes was analyzed by using the TIMER database. The expressions of mucin 5B, oligomeric mucus/gel-forming in clinical NPC tissues and adjacent tissue samples were detected Furthermore, mucin 5B, oligomeric mucus/gel-forming abnormal expression vectors were constructed and transfected into human NPC cell CNE-2Z to detect alterations in cell activity, ferroptosis and the immune microenvironment. In addition, the role of the Wnt/β-catenin signaling pathway in nasopharyngeal carcinoma was observed, and the influence of mucin 5B, oligomeric mucus/gel-forming on this pathway was discussed. Results A total of 42 differentially expressed genes were found in the GSE227541 dataset, among which mucin 5B, oligomeric mucus/gel-forming was obviously at the core of the entire network. In nasopharyngeal carcinoma tissues, the research team observed the upregulated expression of mucin 5B, oligomeric mucus/gel-forming (P < 0.05). In vitro, increased expression of elevated mucin 5B, oligomeric mucus/gel-forming activates nasopharyngeal carcinoma cell activity and immune escape and inhibits ferroptosis. In terms of pathways, upregulating mucin 5B, oligomeric mucus/gel-forming expression could activate the Wnt/β-catenin pathway. Conclusions Mucin 5B, oligomeric mucus/gel-forming regulates the immune escape of nasopharyngeal carcinoma cells and participates in tumor progression by mediating the Wnt/β-catenin signaling pathway.